2019
DOI: 10.3390/ijerph16234874
|View full text |Cite
|
Sign up to set email alerts
|

Nothing Like Living with a Family: A Qualitative Study of Subjective Well-Being and its Determinants among Migrant and Local Elderly in Dongguan, China

Abstract: Chinese economic development has led to a significant rise in internal migration over the last 20 years, including large numbers of elderly. When elderly Chinese people migrate, they still register their residency to their place of origin and often do not register with the new administrative office at the destination due to the household registration (hukou) system in China. Thus, most of these migrant elderly do not receive full social services, possibly leading to poor subjective well-being. This study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 49 publications
5
31
0
1
Order By: Relevance
“…This may be related to the prevalence of diseases; when living with family members, chronic diseases such as heart disease and stroke may have a great impact on elderly people's self-rated health. However, most of the MEFC in the survey sample were living with their family members, and their families' support and care may have resulted in a high level of health and life satisfaction, which is similar to the results of previous studies [45][46][47]. Our study is similar to a previous study which also found that children were identified as the most important source of financial and comfort support, followed by relatives and spouses [48].…”
Section: Association Between Social Support and Self-rated Healthsupporting
confidence: 89%
“…This may be related to the prevalence of diseases; when living with family members, chronic diseases such as heart disease and stroke may have a great impact on elderly people's self-rated health. However, most of the MEFC in the survey sample were living with their family members, and their families' support and care may have resulted in a high level of health and life satisfaction, which is similar to the results of previous studies [45][46][47]. Our study is similar to a previous study which also found that children were identified as the most important source of financial and comfort support, followed by relatives and spouses [48].…”
Section: Association Between Social Support and Self-rated Healthsupporting
confidence: 89%
“…Compared with community-dwelling elderly in Zhejiang, China [ 48 ], the MCS scores of MEFC were higher and PCS scores were similar. This may be because family reunions are beneficial to the mental health of the migrant elderly [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subjective well-being (SWB) represents a person's subjective assessment of their quality of life, happiness, and satisfaction, as well as the quality of their experiences with regard to other areas of life (10)(11)(12). SWB can be divided into several dimensions: life satisfaction (global judgments of one's life), satisfaction with important domains (e.g., work satisfaction), positive effect (regularity of experiencing pleasant emotions and moods), and negative effect (regularity of experiencing unpleasant emotions and moods) (13)(14)(15)(16). A study found that migrants who live in Southern Europe, Eastern Europe, and non-European countries have significantly lower levels of SWB than the native populations (17).…”
Section: Introductionmentioning
confidence: 99%